PENERAPAN MANAJEMEN RISIKO DALAM PENGELOLAAN DANA DESA: PERSPEKTIF KONSEPTUAL - Mochamad Muslih (Jurnal Media Birokrasi, 2020)
The administration of village funds has been established by the government since 2014. In addition to having reaped a lot of bene????its, village grants have alsocaused a lot of abuse in the use of village funds. One solution that might hamper the misuse of village funds is the application of integrated risk management. The purpose of this study is to study the application of the concept of risk management in village fund management. The method used is qualitative method with survey approach. 79 (seventy nine) respondents consisting of academics and practitioners were respondents in this study. The results showed that the majority of respondents thought that it was necessary to implement integrated risk management in village fund management. Village fund managers are advised to implement risk management in village fund management. Village fund management organizations to have a chief risk of????icer. Future researchers should examine the bene????its of applying risk management quantitatively. Keywords: village funds, risk management, chief risk of????icer, survey.